オーロラ・オーストラリス ニヨル ダイ50ジタイ デノ ショウワキチ ニオケル ジンイン ブッシ ユソウ - 石沢, 賢二; イシザワ, ケンジ; 水野, 誠; ミズノ, マコト; Ishizawa, Kenji; Mizuno, Makoto (2010)
P(論文) 第50次南極地域観測隊が,2008年-2009年夏期シーズンに行った「オーロラ・オーストラリス(A.A.)」による昭和基地への人員・物資輸送について報告する.南極観測船「しらせ」の運航は,第49次隊行動で終了し,2009年4月で退役した.そのため,第50次隊の人員・物資輸送を行う代替船として,オーストラリアが南極輸送に使用している砕氷船をチャーターした.同船の行動としては,2008/2009年シーズンの第3次航海にあたる.同船は,2008年12月30日に西オーストラリアのフリーマントルを出港し,翌2009年1月12日に昭和基地北方の流氷縁に到着した.ここから第50次越冬隊員28名および建設作業などに従事する第50次夏隊員を3機の小型ヘリコプターで昭和基地に輸送した.さらに同船は,昭和基地から約40マイルの定着氷まで進出し,第50次越冬隊成立に必要な物資と夏期作業用物資約91.8トンの輸送を実施した.その後,2009年2月2日,29名の第49次越冬隊員と第50次夏隊員および隊持ち帰り物資を同船に収容した.同船は,同日ただちに北に向け航海を開始,2月20日にホバート港に到着し,チャーター船による輸送が終了した.総航海日数は53日,氷海域行動日数は23日であった.その後,持ち帰り物資を収容したコンテナは,日本まで洋上輸送された. The personnel and cargo transportation activities in the 2008-2009 austral summer for Syowa Station by the 50th Japanese Antarctic Research Expedition (JARE-50) are reported. The Antarctic operations for 25 years by the first icebreaker "Shirase" ended with the JARE-49 activity and she was retired in April 2009. The third leg of icebreaker "Aurora Australis" in 2008 2009 season was chartered through the Australian Antarctic Division for the supply of JARE-50. The vessel arrived at the edge of drift sea ice on January 12, 2009. JARE-50 wintering personnel (28 persons) and some expeditioners for summer operations such as construction work were transported to the Station. Then, the vessel reached the edge of fast ice at about 40 nautical miles from Syowa Station and continued the transportation by three helicopters on board. The total transported cargo was 91.8 tons. JARE-49 wintering personnel (29 persons), JARE-50 summer persons and cargo were taken in the vessel on February 2, 2009. The voyage lasted 53 days, including 23 days within sea ice. The vessel departed immediately toward the north on that day and arrived in Hobart on February 20. The containers were returned to Japan by sea transportation. departmental bulletin paper